2017
DOI: 10.3389/fphys.2017.00035
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Static Exercises Differentially Affect Plasma Cytokine Content in Elite Endurance- and Strength-Trained Athletes and Untrained Volunteers

Abstract: Extensive exercise increases the plasma content of IL-6, IL-8, IL-15, leukemia inhibitory factor (LIF), and several other cytokines via their augmented transcription in skeletal muscle cells. However, the relative impact of aerobic and resistant training interventions on cytokine production remains poorly defined. In this study, we compared effects of dynamic and static load on cytokine plasma content in elite strength- and endurance-trained athletes vs. healthy untrained volunteers. The plasma cytokine conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Exercise induces an increase in the plasma levels of different cytokines, including IL-6 [44]. In the year 2000, Steenberg et al published the first study to show that the skeletal-muscle activity connected with exercise increases plasmatic IL-6 levels [45]. Following studies showed that the magnitude of this muscle-fiber derived plasma IL-6 elevation caused by exercise correlates with different parameters such as the intensity and duration of the physical activity [46].…”
Section: Schizophrenia Exercise and Il-6mentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise induces an increase in the plasma levels of different cytokines, including IL-6 [44]. In the year 2000, Steenberg et al published the first study to show that the skeletal-muscle activity connected with exercise increases plasmatic IL-6 levels [45]. Following studies showed that the magnitude of this muscle-fiber derived plasma IL-6 elevation caused by exercise correlates with different parameters such as the intensity and duration of the physical activity [46].…”
Section: Schizophrenia Exercise and Il-6mentioning
confidence: 99%
“…This reduction is also related to the intensity and duration of physical exercise as well as other variables such as the fitness levels of the study participants [47]. People who perform regular exercise in their daily lives show lower baseline IL-6 levels compared to those who are sedentary [45].…”
Section: Schizophrenia Exercise and Il-6mentioning
confidence: 99%
“…The elevated level of IL-4 and IL-6 was detected in all athletes, but more expressed increase was observed in swimmers. Kapilevich et al (2017) showed that the level of circulating IL-6 is connected with character of physical load (dynamic or static). 49 The higher elevation of IL-6 level in swimmers can be connected with significant volume and intensity of training.…”
Section: Discussionmentioning
confidence: 99%
“…Kapilevich et al (2017) showed that the level of circulating IL-6 is connected with character of physical load (dynamic or static). 49 The higher elevation of IL-6 level in swimmers can be connected with significant volume and intensity of training. The level of IL-6 is known to be the first response to the volume and type of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…While dynamic exercise seems to be superior to isometric exercise for strength and hypertrophy [21], there is evidence that isometric exercise can increase strength within a limited range of motion specific to that in which the isometric training was performed [22]. Additionally, evidence suggests that also tendon blood volume as well as tendon stiffness adaptations differ between both contraction modes (dynamic vs. isometric) [23].…”
Section: Introductionmentioning
confidence: 99%